0117 Using milk fat-to-protein ratio to evaluate dairy cows energy balance status. (1st October 2016) - Schcolnik, T.
Abstract: The objective of the present study was to establish the association of negative energy balance status of the calving cow with the duration of high daily fat-to-protein ratio (FPR). Such an association could be utilized to evaluate fresh cow's energy balance status. A dairy cow's physiological condition is reflected in the composition of its milk. AfiLab TM is a real-time milk analyzer measuring individual cows' milk fat, protein and lactose contents during each milking. Fat-to-protein ratio is a combination of milk protein production rate with body fat mobilization rate; that is, it reflects energy availability to a cow's body needs of maintenance and production. Negative energy balance (NEB), ketosis, and body condition score losses are related to reduced conception rate and decreased milk yield. Utilizing FPR for evaluation of cows energy status provides valuable indications, which enable prompt intervention and increase economic profit. Daily milk component data, extracted from the ICBA Israeli HerdBook, included 117, 846 observations (days in milk [DIM] periods) of 23, 192 cows at first lactation or more, calving through 2014, in 44 Israeli Holstein herds using Afilab. Analysis was done by SAS®PROC GLIMMIX. Means of FPR up to 50 DIM were calculated for 3 periods: 1–15, 16–35, and 36–50 DIM. Four categories were defined by FPR threshold of 1.4: (1) means of all periods < 1.4, (19, 181 cows); (2) mean of any one period ≥ 1.4 (2979 cows); (3) means of any two periods ≥ 1.4 (779 cows); and (4) means of all three periods ≥ 1.4 (253 cows). The results establish valid associations between production and fertility traits and the duration of NEB after calving. Least squares means of conception to first AI service were 35.34, 31.62, 30.17, and 33.0% for groups 1, 2, 3, and 4, respectively. Differences between groups 2 and 3 vs. group 1 were statistically significant. The least squares means of days open for the same groups were 122, 125, 129, and 128 d, respectively. The least squares means for 180 d milk yield were 7621, 7685, 7636, and 7468 kg, respectively. Differences between groups 1, 2, and 3 vs. group 4 were statistically significant. We concluded that the intensity of the negative effects of NEB on fertility and production variables examined, relates to the duration of NEB after calving. Therefore, real-time detection of NEB per individual cow allows for specific and prompt treatment.